PENGUATAN SUMBER DAYA MANUSIA(SDM) GURU DI YAYASAN INI MEDIA KITA GUNUNG SINDUR BOGOR - Yuwono, Teguh; Rovita, Angga; Nani, Nani; Zulkarnain, Iskandar; Hindriani, Reni (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Partners in this program are the Foundation of Our Media. The main problem faced by partners is the teaching staff of households and not from education. As is well known, In the formation of quality resources, the existence of education is a major factor that must get serious attention from all parties. Changes in education also have an impact on the way of thinking of the Indonesian people. Therefore given the strengthening of teacher human resources at the Foundation Media Kita aims to change the institutions that operate it into a team that is sincere, without conflict and internal competition, to achieve a single goal, which is to satisfy customers. 2 (two) types, i.e. 1). internal customers namely school managers such as teachers, librarians, laboratory assistants, technicians and administrative staff; 1) external customers which are divided into: (a) primary customers, namely students. 2) secondary customers, parents, government and sponsors; (b) primier customers such as universities and the world of work who receive graduates of the Foundation.